Intergenerational transmission of qualities of the parent–child relationship in the population-based Young Finns Study. Issue 4 (4th July 2017) - Savelieva, Kateryna; Keltikangas-Järvinen, Liisa; Pulkki-Råback, Laura; Jokela, Markus; Lipsanen, Jari; Merjonen, Päivi; Viikari, Jorma; Raitakari, Olli T.; Hintsanen, Mirka
Abstract: We examined the intergenerational transmission of parent–child relationship qualities in a population-based Finnish sample of 1418 participants (G2) and their mothers (G1). At baseline, G1 ( M age = 38) reported qualities of the parent–child relationship in terms of emotional warmth and acceptance towards G2 (age range 3–18). After 28 years, G2 ( M age = 39) rated the qualities of the parent–child relationship regarding their own children using the same questionnaire. Emotional warmth and acceptance were transmitted across generations even after controlling for demographic and family characteristics in both generations. The transmission was stronger for emotional warmth than acceptance. For emotional warmth, intergenerational transmission was stronger for men than women. The findings provide evidence for the long-term transmission of parenting quality across generations.